High-strength hot-dip galvanized steel sheet having excellent plating quality, steel sheet for plating, and method for producing same
By forming a specific Mn and Si component concentration curve and Fe plating on the surface of the steel plate, the problems of plating peeling and unplating are solved, the plating quality and surface uniformity of the hot-dip galvanized steel plate are improved, and high strength and excellent Mechanical properties.
Patent Information
- Application Number
- CN202380045430.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-03
AI Technical Summary
Prior Art In the process of hot-dip galvanized steel plate manufacturing, the plating layer is prone to peeling and unplating frequently, resulting in poor plating quality. Especially in high-strength steel plates, the surface oxide is uneven, resulting in poor adhesion of the plating layer. It is difficult to ensure high-quality plating.
By forming a specific Mn and Si component concentration curve on the surface of the steel plate, the distribution of surface oxides is controlled by using Fe plating to ensure that the difference between the maximum and minimum points of Mn and Si is greater than 80% and 50%, and preventing the surface oxides from Formation, thereby improving plating adhesion during hot-dip galvanizing and preventing linear defects after alloying heat treatment.
The plating quality of hot-dip galvanized steel plate is significantly improved, the coating peeling and unplating are avoided, the surface quality is ensured, and the wireless defects are obtained after alloying heat treatment, which improves the mechanical properties of the galvanized steel plate.
Smart Images

Figure CN119256118A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength hot-dip galvanized steel sheet with excellent plating quality, a plated steel sheet for producing the high-strength hot-dip galvanized steel sheet, and methods for producing the same. Background Art
[0002] In recent years, in the automobile industry, high-strength steel sheets have been used as automobile steel materials to improve safety and reduce weight by reducing thickness. Martensitic steel and TRIP steel have been developed as preferred steel materials for automobiles. These high-strength steels are added with various alloy elements compared to ordinary steels, and in particular, many elements with a higher oxidation tendency than Fe, such as Mn, Si, Al, Cr, and B, are added.
[0003] The quality of hot-dip galvanizing is determined by the surface state of the annealed steel sheet before plating. The elements such as Mn, Si, Al, Cr, and B added to ensure the physical properties of the steel sheet cause the formation of surface oxides during the annealing process, thereby deteriorating the plating property. That is, during the annealing process, the elements diffuse to the surface and react with the trace amount of oxygen or water vapor present in the annealing furnace to form a single oxide or a composite oxide of the elements on the surface of the steel sheet, thereby reducing the reactivity of the surface. The annealed steel sheet surface with reduced reactivity will hinder the wettability of the hot-dip galvanizing bath, resulting in unplated areas where the plating metal is not attached locally or entirely on the surface of the plated steel sheet. In addition, due to these oxides, the formation of the alloying inhibition layer (Fe2Al5) necessary to ensure the adhesion of the coating during the hot-dip plating process is insufficient, thereby greatly reducing the plating quality of the plated steel sheet, such as the occurrence of coating peeling.
[0004] Various technologies for improving the plating quality of high-strength hot-dip plated steel sheets have been proposed. Among them, Patent Document 1 proposes a technology that controls the air-fuel ratio of air to fuel to 0.80 to 0.95 during annealing, oxidizes the steel sheet in a direct flame furnace in an oxidizing atmosphere, thereby forming iron oxides containing a single oxide or a composite oxide of Si, Mn or Al at a predetermined depth inside the steel sheet, and then performs reduction annealing of the iron oxide in a reducing atmosphere, and then performs hot-dip galvanizing, thereby providing a hot-dip galvanized steel sheet or an alloyed hot-dip galvanized steel sheet with excellent plating quality.
[0005] As in Patent Document 1, when a method of performing oxidation followed by reduction in an annealing process is used, components with a high affinity for oxygen, such as Si, Mn, and Al, are internally oxidized at a predetermined depth from the surface of the steel sheet, thereby suppressing diffusion to the surface layer, and thus the single oxide or composite oxide of Si, Mn, or Al on the surface layer is relatively reduced, thereby improving wettability with zinc, and thus reducing unplated areas. However, in the case of a steel type to which Si is added, Si is enriched just below the iron oxide during the reduction process, thereby forming a band-shaped Si oxide, and thus peeling occurs in the surface layer portion including the plated layer, that is, peeling occurs at the interface between the reduced iron and the base iron below, and thus there is a problem that it is difficult to ensure the adhesion of the plated layer.
[0006] In addition, as another method for improving the coating property of high-strength hot-dip plated steel sheets, Patent Document 2 proposes a method of maintaining a high dew point in the annealing furnace to internally oxidize easily oxidizable alloy components such as Mn, Si, and Al inside the steel, thereby reducing the oxides externally oxidized on the surface of the steel sheet after annealing to improve the coating property. However, the method according to Patent Document 2 can solve the coating property problem caused by the external oxidation of Si that is easily internally oxidized, but when a large amount of Mn that is relatively difficult to internally oxidize is added, there is a problem that the effect is minimal.
[0007] In addition, even if the plating property is improved by internal oxidation, linear non-plating may occur due to uneven surface oxides formed on the surface, or when alloyed hot-dip galvanized steel sheet (GA steel sheet) is manufactured by alloying heat treatment after plating, linear defects caused by uneven alloying may occur on the surface of the alloyed hot-dip galvanized steel sheet.
[0008] Another prior art is to perform Ni pre-plating before annealing to inhibit the diffusion of alloy elements to the surface during annealing. However, although this method is effective in inhibiting the diffusion of Mn, it has the problem of not being able to fully inhibit the diffusion of Si.
[0009] [Prior art literature]
[0010] [Patent Document]
[0011] (Patent Document 1) Korean Patent Publication No. 2010-0030627
[0012] (Patent Document 2) Korean Patent Publication No. 2009-0006881 Summary of the invention
[0013] 1. Technical issues to be resolved
[0014] According to one aspect of the present invention, there is provided a hot-dip galvanized steel sheet having excellent plating quality with no unplated coating and no peeling of the plating layer, and a method for producing the same.
[0015] According to another aspect of the present invention, a hot-dip galvanized steel sheet and a method for manufacturing the same are provided, wherein the hot-dip galvanized steel sheet does not generate linear defects even when alloying heat treatment is performed after plating, thereby being able to produce an alloyed hot-dip galvanized steel sheet having excellent surface quality.
[0016] According to another aspect of the present invention, there is provided a steel sheet for plating and a method for manufacturing the same, the steel sheet for plating being capable of manufacturing a hot-dip galvanized steel sheet having excellent plating quality as described above.
[0017] The technical problems of the present invention are not limited to the above contents. Those skilled in the art to which the present invention belongs can easily understand the additional technical problems of the present invention from the overall content of this specification.
[0018] (II) Technical solution
[0019] According to one aspect of the present invention, a plated steel sheet has a composition comprising, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, Cr: 1.5% or less, B: 0.005% or less, the balance Fe and inevitable impurities, and a GDS curve of the Mn component and a GDS curve of the Si component observed in a depth direction from the surface respectively include a maximum point and a minimum point in sequence. The difference between the value obtained by dividing the Mn concentration at the maximum point of the GDS curve of the Mn component by the Mn concentration of the base material and the value obtained by dividing the Mn concentration at the minimum point of the GDS curve of the Mn component by the Mn concentration of the base material (the converted concentration difference of Mn) can be 80% or more, and the difference between the value obtained by dividing the Si concentration at the maximum point of the GDS curve of the Si component by the Si concentration of the base material and the value obtained by dividing the Si concentration at the minimum point of the GDS curve of the Si component by the Si concentration of the base material (the converted concentration difference of Si) can be 50% or more.
[0020] When no local point appears within a depth of 5 μm, the position at a depth of 5 μm is regarded as the position where the local point appears.
[0021] A hot-dip galvanized steel sheet according to another aspect of the present invention may include the above-mentioned steel sheet for plating and a hot-dip galvanized layer formed on the steel sheet for plating.
[0022] A method for manufacturing a plated steel sheet according to another aspect of the present invention may include the following steps: preparing a base iron having a composition, in weight %, of Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: less than 0.04%, S: less than 0.015%, Cr: less than 1.5%, B: less than 0.005%, the balance of Fe and inevitable impurities; electroplating the base iron to form a Fe coating containing 5-50 weight % of oxygen; and annealing the base iron forming the Fe coating at 600-950° C. for 5-120 seconds in an annealing furnace in an atmosphere of 1-70% H2-balance N2 gas with a dew point temperature controlled at -15° C. to +30° C.
[0023] A method for manufacturing a hot-dip galvanized steel sheet according to another aspect of the present invention may include the following steps: preparing a base iron having a composition, in terms of weight %, of Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities; electroplating the base iron to form An Fe coating containing 5-50 wt% of oxygen; annealing a base iron forming the Fe coating in an annealing furnace in an atmosphere of 1-70% H2-balance N2 gas with a dew point temperature controlled at -15°C to +30°C at 600-950°C for 5-120 seconds to obtain a plated steel sheet; and immersing the plated steel sheet in a galvanizing bath composed of Al: 0.1-0.3%, balance Zn and inevitable impurities, and maintained at a temperature range of 440-500°C.
[0024] (III) Beneficial effects
[0025] As described above, the present invention can provide a hot-dip galvanized steel sheet that significantly improves the non-plating phenomenon that occurs during hot-dip galvanizing and improves the plating adhesion by forming a pre-plating layer and controlling the concentration profile of the internal Mn and Si components.
[0026] In addition, according to one aspect of the present invention, even if the hot-dip galvanized steel sheet of the present invention is subjected to alloying heat treatment, linear defects on the surface of the obtained alloyed hot-dip galvanized steel sheet can be prevented, thereby providing an alloyed hot-dip galvanized steel sheet with excellent surface quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the GDS curve measured after removing the coating of the hot-dip galvanized steel sheet produced by the cold-rolled steel sheet electroplated with Fe.
[0028] Figure 2 This is a schematic diagram of a process in which the base iron on which the oxygen-containing Fe plating layer is formed is annealed in a high dew point atmosphere. DETAILED DESCRIPTION
[0029] Hereinafter, a high-strength hot-dip galvanized steel sheet having excellent plating quality according to one aspect of the present invention completed by the inventor's research is described in detail. It should be noted that when the concentration of each element is expressed in the present invention, it is expressed by weight % unless otherwise defined. In addition, the Fe electroplating amount is the plating amount measured by the total amount of Fe contained in the coating per unit area, and oxygen and unavoidable impurities in the coating are not included in the plating amount.
[0030] In addition, unless otherwise defined, the concentration and concentration curve mentioned in the present invention refer to the concentration and concentration curve measured by using GDS, that is, using a glow discharge optical emission spectrometer.
[0031] Hereinafter, the present invention will be described in detail.
[0032] It is known that the reason why non-plating and reduced plating adhesion occur in steel sheets containing a large amount of Mn and Si is due to surface oxides generated by oxidation of alloy elements such as Mn and Si on the surface during annealing of the cold-rolled steel sheets at high temperatures.
[0033] As a method for suppressing the diffusion of alloying elements such as Mn and Si to the surface to form an oxide layer containing a large amount of oxygen, a redox method of oxidizing during the heating process and then maintaining it in a reducing atmosphere for reduction or a method of coating the surface of the base metal with iron oxide and performing heat treatment can be used. However, the iron oxide firmly formed on the surface of the base metal contains not only FeO but also Fe3O4 and Fe2O3 that are difficult to reduce, and the surface is reduced to metallic iron during annealing in a reducing atmosphere. On the other hand, the reduction rate of the interface between the iron oxide layer and the base iron is slow, so it is difficult to completely reduce, and the oxides of Mn and Si accumulate at the interface to form a continuous oxide layer. Therefore, although the wettability with molten zinc can be improved, the oxide layer is easily broken and the problem of plating peeling may occur.
[0034] In addition, when an annealing internal oxidation method is used in which alloying elements such as Mn and Si are oxidized inside the steel by increasing the oxygen partial pressure or dew point in the annealing furnace during the heat treatment process, Mn and Si oxides are preferentially formed on the surface of the steel during the heat treatment process, and then Mn and Si are oxidized by oxygen diffused into the steel, thereby inhibiting surface diffusion. Therefore, a thin oxide film is formed on the surface of the base iron, and when the surface of the cold-rolled steel sheet before annealing is not completely homogeneous or there are local deviations in oxygen partial pressure, temperature, etc., there is a tendency to cause linear defects that can be easily recognized by visual inspection when the wettability is uneven during hot-dip galvanizing and non-plating occurs, or when the thickness of the oxide film is uneven during the alloying heat treatment after galvanizing and a difference in the degree of alloying occurs.
[0035] In order to solve the above technical problems, the present inventors attempted to manufacture a hot-dip galvanized steel sheet having a fine surface and free from the problem of plating peeling by controlling the existence form of Mn and Si as oxidizing elements on the surface side of the steel sheet for plating as follows.
[0036] That is, the GDS concentration curve of Mn and Si of the steel sheet according to one specific embodiment of the present invention may have the following characteristics. Figure 1 The GDS curve of the present invention is used to explain the steel sheet for coating in detail.
[0037] Figure 1 Schematically shows a typical GDS curve of Mn components that may appear on the surface of a hot-dip galvanized steel sheet including the steel sheet of the present invention after the galvanized layer is removed. In the figure, the vertical axis represents the concentration of alloying elements such as Mn and Si, and the horizontal axis represents the depth. Figure 1 As shown in the figure, the concentration curve of the Mn component or Si component of the plated steel sheet of the present invention may have a form in which a maximum point and a minimum point appear in sequence from the surface (the interface with the coating when hot-dip galvanized) toward the inside. The sequential appearance here does not mean that the maximum point must appear first along the depth direction from the surface (interface). Depending on the situation, the minimum point may appear first, but this means that the maximum point and the minimum point will appear in sequence later. However, in some specific embodiments, the minimum point may not appear. In this case, the internal concentration of the area with a depth of 5 μm can be set to the minimum point concentration. In addition, the concentration of the alloying element on the surface may have a value less than the concentration of the maximum point, but depending on the situation, a minimum point with a low concentration of the alloying element may also appear between the surface and the maximum point.
[0038] In using the Figure 1In the illustrated GDS concentration curve, although not necessarily limited to this, the surface layer portion corresponds to the Fe plating where the alloy element does not diffuse in large quantities from the base iron and the concentration of the alloy element is low, the maximum point corresponds to the region where the internal oxide of the alloy element formed near the interface between the Fe plating and the base iron is concentrated, and the minimum point appearing on the base iron side in the Fe plating corresponds to the region where the alloy element diffuses into the Fe plating that does not contain the alloy element and is diluted, or the alloy element diffuses to the maximum point where internal oxidation occurs and is depleted.
[0039] In a specific embodiment of the present invention, the maximum point can be formed at a depth of 0.05-1.0 μm from the surface of the steel plate. When the maximum point appears in an area deeper than this depth, it may not be judged as a maximum point caused by the effect of the present invention. In addition, the minimum point can be formed at a position within a depth of 5 μm from the surface of the steel plate. As described above, when the minimum point is not formed at a position within a depth of 5 μm, the depth of 5 μm can be set as the position where the minimum point is formed. The concentration at a depth of 5 μm is substantially the same as the concentration of the base material, so it can be regarded as a position where the concentration no longer decreases.
[0040] At this time, in the Mn concentration curve and the Si concentration curve, the greater the difference between the converted concentration of the element at the maximum point (the value of dividing the concentration at the position by the concentration of the base material, expressed in %) and the converted concentration at the minimum point, the less Mn and Si diffused to the surface can be, so it is very important. In a specific embodiment of the present invention, in the case of Mn, the value of the maximum point conversion concentration-the minimum point conversion concentration can be more than 80%, and in the case of Si, the difference between the values can be more than 50%. Si is an element with stronger oxidizing properties than Mn, and it is easy to cause internal oxidation even inside the substrate iron with low oxygen concentration, so oxidation can occur in a wider area than Mn. Therefore, even if the difference between the converted concentrations of the maximum point and the minimum point of Si is less than the difference between the converted concentrations of the maximum point and the minimum point of Mn, it cannot be considered that the degree of internal oxidation of Si is small. The results of the experiments conducted by the inventors with various conditions show that when the above conditions are met, a hot-dip galvanized steel sheet can be obtained that does not undergo unplating during hot-dip galvanizing and has good plating adhesion. However, when the difference between the converted concentrations of the maximum and minimum points of Mn is less than 80% or the difference between the converted concentrations of the maximum and minimum points of Si is less than 50%, there may be a problem of point-like or linear unplating or coating peeling. That is, by the conditions as described above, it is possible to prevent the generation of Mn and Si oxides on the surface, so that an ultra-high strength hot-dip galvanized steel sheet with a fine surface and good plating adhesion can be manufactured, and even after subsequent alloying heat treatment processes, defects such as linear defects on the surface can be suppressed. The greater the difference in the converted concentration values, the more favorable it is, so there is no need to set an upper limit on the value. However, considering the content of the elements contained, in the case of Mn, the difference in the converted concentration values can be set to less than 400%, and in the case of Si, the difference in the converted concentration values can be set to less than 250%. In another specific embodiment of the present invention, the converted concentration difference of Mn can be set to more than 90% or more than 100%, and the converted concentration difference of Si can be set to more than 60% or more than 70%.
[0041] Hereinafter, the GDS analysis method performed in the present invention will be described in detail.
[0042] For GDS concentration analysis, the hot-dip galvanized steel sheet is cut into a length of 30-50 mm and immersed in a 5-10 wt% hydrochloric acid aqueous solution at a room temperature of 20-25°C to remove the galvanized layer. In order to prevent damage to the surface of the base iron during the dissolution of the galvanized layer, when the generation of bubbles caused by the reaction of the galvanized layer and the acid solution stops, the acid solution is removed within 10 seconds, and the base iron is washed with pure water and dried. Of course, if the steel sheet is not hot-dip galvanized, the analysis can be performed even without such removal of the coating.
[0043] The GDS concentration curve measures the concentration of all components contained in the steel plate at intervals of 1-5 nm in the thickness direction of the steel plate. The measured GDS curve may contain irregular noise. In order to calculate the maximum and minimum points of Mn and Si concentrations, a Gaussian filter with a cutoff value of 100 nm is applied to the measured concentration curve to obtain an average concentration curve, and the concentration values and depths of the maximum and minimum points of the concentration are respectively obtained from the noise-removed curve. In addition, it should be noted that the maximum and minimum points mentioned in the present invention are calculated as maximum and minimum points only when they differ from each other by more than 10 nm in the depth direction.
[0044] The plated steel sheet used as the subject of the present invention may include a base iron and an Fe plating layer formed on the base iron. The composition of the base iron is not particularly limited.
[0045] However, when the high-strength steel sheet contains 1.0-8.0 wt % of Mn and 0.05-3.0 wt % of Si and has a composition that is easy to generate oxides on the surface, the coating property can be advantageously improved by the present invention. The upper limit of the Mn concentration of the substrate iron is not particularly limited, but considering the commonly used composition, the upper limit can be limited to 8 wt %. In addition, the lower limit of the Mn concentration is not particularly limited, but in the case of a composition containing less than 1.0 wt %, even if the Fe coating is not formed, the surface quality of the hot-dip galvanized steel sheet is also very fine, so there is no need to perform Fe electroplating. The upper limit of the Si concentration is not particularly limited, but considering the commonly used composition, the upper limit of the Si concentration can be limited to less than 3.0 wt %, and when the Si concentration is less than 0.05 wt %, even if Fe electroplating and annealing internal oxidation are not performed at the same time, the hot-dip galvanizing quality is also very fine, so there is no need to perform the method of the present invention.
[0046] The Mn and Si mentioned above are elements that affect the plating properties, and therefore their concentrations may be limited as described above, but the present invention does not particularly limit the other components of the base material iron.
[0047] However, considering that in the case of a high-strength steel sheet containing a large amount of alloy components, serious unplating and reduction in plating adhesion may occur, in a specific embodiment of the present invention, the composition of the base iron may include, by weight%, Mn: 1.0-8.0%, Si: 0.05-3.0%, C: 0.06-0.3% (preferably 0.07-0.4%, more preferably 0.08-0.4%), Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, the balance of Fe and inevitable impurities. P, S and N are impurities, and the less they are added, the more advantageous it is. Cr and B are optional elements, and it is not harmful even if they are not added, so the lower limit is not individually defined.
[0048] The composition of the steel of the present invention will be described in more detail below. Unless otherwise indicated, the content of each element is based on weight.
[0049] Mn: 1.0-8.0%
[0050] Manganese (Mn) is an element added to ensure strength. When the Mn content is less than 1.0%, it is difficult to ensure strength. On the other hand, when the Mn content exceeds 8.0%, the bainite phase transformation rate slows down, too much new martensite is formed, and it is difficult to obtain high hole expansion. In addition, due to the segregation of Mn, a banded structure is formed, which impairs the material uniformity and formability of the material. Therefore, the Mn content is preferably in the range of 1.0-8.0%. The lower limit of the Mn content is more preferably 1.5%.
[0051] Si: 0.05-3.0%
[0052] Silicon (Si) is a useful element for improving the strength of steel sheets by solid solution strengthening and precipitation hardening. The silicon (Si) inhibits the formation of cementite, and therefore has the effect of promoting C enrichment in austenite, and is an essential element for improving the strength and elongation of steel by generating retained austenite after annealing. When the content of Si exceeds 3.0%, the physical properties of the weld are deteriorated due to LME cracks, and the surface characteristics and coating properties of the steel are deteriorated. Therefore, the content of Si preferably has a range of 0.05-3.0%.
[0053] C: 0.06-0.4%
[0054] Carbon (C) is an element that ensures the strength of steel by solid solution strengthening and precipitation strengthening, and is an effective element that ensures high ductility by stabilizing retained austenite. When the C content is less than 0.05%, a tensile strength of 1500MPa cannot be obtained, and when the C content exceeds 0.4%, a steel sheet cannot be manufactured by cold rolling. Therefore, the C content is preferably 0.06-0.4%. On the other hand, the C content is more preferably in the range of 0.2% or more and 0.4% or less.
[0055] Al: 0.005-3.0%
[0056] Aluminum (Al) is an element having a deoxidizing effect on molten steel, and similarly to Si, plays a role in improving the stability of austenite, and is effective in improving elongation.
[0057] When the Al content is less than 0.005%, deoxidation of the steel cannot be fully achieved, and the cleanliness of the steel is impaired. On the other hand, when the Al content is too much, the phase transformation temperature rises significantly, and the fraction of ferrite increases, so that high strength cannot be achieved. Therefore, the Al content is set to 3.0% or less. In another specific embodiment of the present invention, the Al may be limited to 2.0% or less, or the Al may be limited to 1.0% or less.
[0058] P: 0.04% or less
[0059] Phosphorus (P) is contained as an impurity and segregates at the grain boundaries, thereby reducing toughness. Therefore, it is preferred to control the phosphorus content as low as possible. In addition, when the P is added excessively, the toughness of the steel material deteriorates, so in order to prevent this in the present invention, it is preferred to limit the upper limit of the P to 0.04%. In the present invention, the less P is added, the more advantageous it is, so there is no need to specifically set a lower limit for the P content. However, considering conventional manufacturing methods, the lower limit of the P content may also be set to 0.002%. In a specific embodiment of the present invention, the upper limit of the P content may also be set to 0.0173%.
[0060] S: 0.01% or less
[0061] Similar to P, sulfur (S) is contained in steel as an impurity. S combines with Mn to form inclusions, which may reduce hole expandability and may also reduce weldability and hot rolling properties, so it is advantageous to control the sulfur content as low as possible. Therefore, considering the situation where S is inevitably included, the S content can be limited to less than 0.01%. In the present invention, the less S is added, the more advantageous it is, so there is no need to specifically set a lower limit for the S content. However, considering conventional manufacturing processes, the lower limit of the S content can also be set to 0.0009%. In another specific embodiment of the present invention, the upper limit of the S content can be set to 0.0021%.
[0062] N: 0.01% or less
[0063] In the present invention, nitrogen (N) is contained in the steel as an impurity, and it is advantageous to control the content of the nitrogen (N) to be as low as possible. Therefore, in a specific embodiment of the present invention, the N can be limited to less than 0.01%, and the lower limit is not particularly set. However, considering the situation where N is inevitably included, 0% (i.e., more than 0%) can be excluded. In another specific embodiment of the present invention, the lower limit of the N content can also be set to 0.0005%. In addition, in another specific embodiment of the present invention, the upper limit of the N content can be set to 0.007%, or it can be set to 0.006% or 0.0052%.
[0064] Cr: less than 1.5%
[0065] Chromium (Cr) is an effective element for improving strength. The chromium (Cr) suppresses the formation of carbides, making it easy to ensure retained austenite. On the other hand, when the Cr content exceeds 1.5%, local corrosion resistance deteriorates and surface oxides are formed, thereby impairing phosphate treatment properties. Therefore, the Cr content preferably has a range of 1.5% or less. The Cr content is more preferably 1.0% or less.
[0066] B: 0.005% or less
[0067] Boron (B) strengthens the grain boundaries and suppresses the ferrite phase transformation during the cooling process after annealing. In order to obtain this effect, the addition amount of B can be set to 0.0001% or more. When the addition amount of B is too much, the hot rolling property is reduced, and B accumulates excessively on the surface, thereby hindering the plating property. Therefore, the B content preferably has a range of 0.005% or less.
[0068] In the present invention, high strength means a case where high strength is obtained after annealing, and also includes a case where high strength can be obtained through heat treatment in subsequent processes. In addition, in the present invention, high strength may refer to a tensile strength of 490 MPa or more, but is not limited thereto. In addition to the above-mentioned components, the base iron may further contain elements such as Ti, Mo, Nb, etc., totaling less than 1.0%. There is no particular limitation on the base iron, but in a specific embodiment of the present invention, a cold-rolled steel sheet or a hot-rolled steel sheet may be used as the base iron. In addition, although not necessarily limited thereto, in a specific embodiment, the cold-rolled steel sheet or the hot-rolled steel sheet may use martensitic steel or TRIP steel.
[0069] In a specific embodiment of the present invention, the cold-rolled steel sheet or the hot-rolled steel sheet may have a fine structure, and the fine structure includes: 30-70 volume % of tempered martensite, 5-45 volume % of bainite, 10-40 volume % of retained austenite, and 20 volume % or less of ferrite phase. The fine structure can have high strength while ensuring hole expansion by including more than 30 volume % of tempered martensite. In addition, when more than 10 volume % of retained austenite is included, the phase transformation induced plasticity phenomenon caused by the retained austenite can be utilized, thereby greatly improving the elongation. Bainite is included to form retained austenite and ensure strength, and more than 5 volume % of bainite needs to be included. Ferrite can be included as needed to improve mechanical properties by improving elongation and refining old austenite grains, and stabilize the retained austenite by increasing the C enrichment in the retained austenite. However, when the proportion of the ferrite phase exceeds 20% by volume, the interphase hardness difference with the tempered martensite as the matrix structure becomes large, and the bendability and hole expandability may deteriorate, so the proportion of the ferrite phase may be limited to 20% by volume or less. Depending on the situation, the ferrite phase may be contained in an amount of 3% by volume or more. When the proportion of each phase is too high, the proportion of other phases may be limited to less than an appropriate range, so the upper limit may be limited as described above.
[0070] The hot-rolled steel sheet or cold-rolled steel sheet having the above-mentioned fine structure is not necessarily limited thereto, but can be manufactured by the following process.
[0071] That is, a hot rolled steel plate can be manufactured by a process comprising the following steps: heating a steel billet, wherein the steel billet contains, in weight %, Mn: 1.0-8.0%, Si: 0.05-3.0%, C: 0.06-0.4% (preferably 0.07-0.4%, more preferably 0.08-0.4%), Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.0% or less, Cr: 1.5% or less, B: 0.005% or less, the balance Fe and inevitable impurities; hot rolling the heated steel billet to obtain a steel plate; and coiling the hot rolled steel plate. In addition, in the case of a cold-rolled steel sheet, it can be manufactured by a process comprising the following steps: cold rolling the hot-rolled steel sheet; keeping the cold-rolled steel sheet in a soaking zone (soaking section) for 50-500 seconds; cooling the kept steel sheet at a cooling rate of more than 1°C / second (depending on the situation, it can be limited to less than 3000°C / second, less than 2000°C / second or less than 1000°C / second) to a temperature between 100-300°C; heating the cooled steel sheet to a temperature between 300-600°C and keeping it for more than 50 seconds (depending on the situation, it can be limited to less than 3000 seconds or less than 2000 seconds).
[0072] In one aspect of the present invention, a hot-dip galvanized steel sheet including the plated steel sheet may be provided, and the hot-dip galvanized steel sheet may include the plated steel sheet and a hot-dip galvanized layer formed on the surface of the plated steel sheet. In this case, any commonly used hot-dip galvanized steel sheet may be used as the hot-dip galvanized steel sheet, and the type thereof is not particularly limited.
[0073] Next, an exemplary specific embodiment of a method for manufacturing a plated steel sheet and a hot-dip galvanized steel sheet having the above-mentioned advantageous effects is described. According to a specific embodiment of the present invention, the plated steel sheet can be manufactured by a process comprising the following steps: preparing a base iron; electroplating the base iron to form an Fe plating layer containing 5-50 wt % of oxygen; annealing the base iron forming the Fe plating layer to obtain a plated steel sheet.
[0074] A 1.2GPa grade cold rolled steel sheet (martensitic steel) containing 2.3% Mn, 0.9% Si and other alloying elements was annealed for 53 seconds in an atmosphere of N2-5% H2, a dew point of +5°C, and a temperature of 800°C, and then observed with a transmission electron microscope. The same atmosphere was maintained throughout the heating period, and the dew point temperature was maintained at -40°C during cooling to prevent Fe from being oxidized. It was divided into Fe electroplating containing 6.6% by weight of oxygen before annealing to make the iron adhesion amount as a reference 2.02g / m 2 The cases where the above-mentioned Fe electroplating was performed and the cases where the above-mentioned Fe electroplating was not performed were compared, and the phenomena that occurred were observed.
[0075] The observation results show that fine Mn oxide and Si oxide are observed from the surface layer of the steel sheet that is not Fe-plated and annealed at a dew point of +5°C, and thick grain boundary oxides are formed inside the base iron. This is because the cold rolled structure begins to form grain boundary oxides from the step of recovery and recrystallization into fine grains during the heating process, and as the annealing temperature increases and the annealing time increases, oxygen is introduced into the base iron with coarsened grains to generate oxides around the grain boundaries. This form ultimately causes the concentrations of the Mn component and the Si component in the GDS curve to change slowly, and the maximum and minimum points cannot appear smoothly, or even if the maximum and minimum points appear, the difference in the converted concentration cannot meet the limited range in the present invention.
[0076] However, when the Fe plating layer containing 5-50 wt% of oxygen is plated so that the iron deposition amount becomes 1.99 g / m 2When annealing is performed afterward, almost no oxide is generated in the Fe coating area, and granular oxide is generated at the interface between the Fe coating and the base iron and inside the base iron, and this oxide acts as the nucleus of the internal oxide and grows into a linear oxide in a direction perpendicular to the surface of the steel sheet. However, in terms of the depth of the internal oxide generation, compared with the case where the Fe coating is performed, the oxide is generated at a deeper depth when the Fe coating is not formed. In the case as described above, there are less Mn components and Si components in the Fe coating (surface layer), and not only a maximum value can appear at the interface, but also a depletion layer can be provided in which the Mn content and Si content in the region deeper than the maximum value are greatly reduced.
[0077] In addition, when Fe plating is not performed and annealing is performed in a high dew point atmosphere, oxides are generated from the surface of the base iron to the grain boundaries of the fine recrystallized structure to inhibit crystal growth, thereby generating irregular fine grains surrounded by fine oxides. On the other hand, when annealing is performed at a high dew point of -15°C to +30°C after forming a plating layer with a high oxygen content, the Fe plating layer does not contain oxidizing alloy elements such as Mn and Si, so no oxides are generated at the grain boundaries of the plating layer, and oxides are generated at the interface between the Fe plating layer and the base iron, so it has the characteristics of being divided into a Fe plating structure of uniform thickness and grains inside the base iron. However, depending on the dew point in the annealing furnace, the elongation of the base iron, the steel composition, etc., there are cases where the boundary between the Fe plating layer and the base iron is not clear. Therefore, after Fe electroplating, even if the dew point in the annealing furnace is controlled to -15°C to +30°C, it does not necessarily have the above-mentioned characteristics.
[0078] Unlike the redox method, the annealing internal oxidation method does not form a layered oxide layer. Therefore, when hot-dip galvanizing ultra-high-strength steel sheets containing a large amount of alloying elements such as Mn and Si, it shows excellent characteristics in improving plating adhesion. However, the water vapor in the annealing furnace will inevitably preferentially oxidize the surface of the steel sheet, and then oxygen will penetrate into the interior, so the surface oxide cannot be fundamentally removed.
[0079] In order to solve the above problems, the inventors have found through a large number of experiments that when annealing is performed in a high dew point atmosphere after forming an Fe coating containing a large amount of oxygen, the oxygen in the water vapor in the annealing furnace will not form surface oxides of alloy elements such as Mn and Si on the surface of the Fe coating, and the situation in which the oxygen contained in the Fe coating causes the alloy elements such as Mn and Si in the base iron to be internally oxidized and diffused to the surface can be effectively suppressed. The oxygen introduced into the steel due to the high dew point in the annealing furnace will further internally oxidize the alloy elements, so that the surface oxides of the alloy elements are almost not generated on the surface of the steel, thereby significantly improving the surface quality and plating adhesion of the hot-dip galvanized steel sheet, and also promoting the alloying reaction when manufacturing the alloyed hot-dip galvanized steel sheet, so that a uniform alloyed hot-dip galvanized steel sheet without surface defects can be obtained.
[0080] In more detail, when an Fe plating layer containing 5-50 wt% of oxygen is formed on a cold-rolled steel sheet (base iron), and the temperature is raised to 600-950°C in an annealing furnace with a dew point controlled at -15°C to +30°C to ensure the mechanical physical properties of the steel sheet, and then cooled again and hot-dip plated, a hot-dip plated steel sheet with suppressed non-plating and excellent plating adhesion can be obtained.
[0081] In a specific embodiment of the present invention, the Fe coating can be formed by a continuous coating process, and based on the Fe adhesion amount, the Fe coating amount at this time can be 0.5-3.0 g / m 2 When the Fe coating amount is less than 0.5g / m 2 When the amount of Fe plating exceeds 3.0 g / m, the effect of suppressing the diffusion of alloy elements by Fe plating in the usual continuous annealing process may be insufficient. 2 , and the inhibition effect of alloying elements can be further improved. However, in order to ensure a high plating amount, multiple plating units need to be used, and when an insoluble anode is used, the electroplating solution will quickly acidify and reduce the plating efficiency, and there is a problem of sludge generation, so it is not economical. In another specific embodiment of the present invention, the Fe plating amount can be 1.0-2.0 g / m 2 When the Fe coating is formed and internal oxidation is performed, internal oxides are formed at the interface between the Fe coating and the substrate iron or just below the interface, so the maximum points of Mn and Si concentration exist in the region of 0.05-1.0 μm. 2 The Fe plating amount may correspond to a thickness of 0.05-0.4 μm after annealing.
[0082] In addition, the Fe coating with the above-mentioned high oxygen concentration forms a maximum point and a minimum point in the GDS concentration curve of the Mn and Si elements inside the plated steel sheet by controlling the temperature, dew point temperature and atmosphere of the subsequent annealing process, and the converted concentration at the maximum point and the converted concentration at the minimum point can meet the numerical range limited in a specific embodiment of the present invention. Taking this into account, in a specific embodiment of the present invention, the oxygen concentration in the Fe coating can be 5-50% by weight, and in another specific embodiment, the oxygen concentration in the Fe coating can be 10-40% by weight. In order to obtain the effect of inhibiting surface oxides, the oxygen content in the Fe coating needs to be sufficient. Although the oxygen concentration in the Fe coating is less than 5% by weight, the effect of inhibiting surface oxides can also be obtained by increasing the Fe coating amount, but in order to obtain the above-mentioned effect, it is necessary to carry out more than 3.0 g / m 2 of plating, so the above-mentioned various problems may occur. In addition, when the oxygen content does not reach 5 wt %, it is difficult to form a maximum point and a minimum point in the GDS curve of Mn and Si in sequence, so in a specific embodiment of the present invention, the oxygen content in the Fe coating is controlled to be more than 5 wt %. In addition, although the inhibitory effect of the surface oxide in the annealing process can be further increased as the oxygen concentration in the Fe coating increases, it is difficult to obtain a coating exceeding 50 wt % by a common electroplating method, so the upper limit of the oxygen concentration in the Fe coating can be limited to 50 wt %. In another specific embodiment of the present invention, the oxygen concentration in the Fe coating can be limited to 10-40%.
[0083] In a specific embodiment of the present invention, the annealing temperature can be 600° C. to 950° C. based on the temperature of the steel sheet in the soaking zone. When the annealing temperature is too low, the structure of the cold-rolled steel sheet cannot be properly restored and recrystallized, so it is difficult to ensure the mechanical and physical properties of the steel sheet, such as strength and elongation. When the annealing temperature exceeds 950° C., the alloy elements in the steel diffuse rapidly to the surface, resulting in poor quality of hot-dip galvanizing, and unnecessary operation at high temperature, which is uneconomical.
[0084] In addition, in one specific embodiment of the present invention, the dew point inside the annealing furnace can be -15°C to +30°C. When the dew point is lower than -15°C, the amount of oxygen introduced into the steel is reduced, thereby only aggravating the surface oxidation and not causing the internal oxidation, so that a large amount of oxides exist on the surface and the quality of hot-dip galvanizing deteriorates. In addition, even if the dew point exceeds +30°C, the effect of suppressing the surface oxidation by increasing the internal oxidation and suppressing the diffusion of alloying elements is further increased, but the supply of water vapor increases sharply, so it is necessary to unnecessarily increase the capacity of the humidification equipment, and when the cooled water vapor is condensed and applied to continuous annealing for a long time, equipment problems may occur. The dew point can be managed in the above range at 600-950°C, and can be managed in a more relaxed condition in a temperature range lower than the above temperature range. In another specific embodiment of the present invention, the dew point can also be limited to -10°C to +20°C.
[0085] In addition, in order to prevent oxidation of the substrate iron and the Fe coating during annealing, the hydrogen concentration in the atmosphere gas during annealing can be set to more than 1% by volume. When the hydrogen concentration is less than 1%, it is impossible to effectively oxidize and remove the trace oxygen inevitably contained in the H2 and N2 gases and increase the oxygen partial pressure, so it may cause surface oxidation of the substrate iron. In addition, when the hydrogen concentration exceeds 70%, the risk of explosion during gas leakage and the cost increase caused by high hydrogen operation, so the hydrogen concentration can be set to less than 70%. In addition to the hydrogen (H2), the gas other than the impurity gas inevitably contained can be nitrogen (N2) in essence.
[0086] In addition, according to a specific embodiment of the present invention, the holding time after reaching the target temperature during annealing can be limited to 5-120 seconds. In order to fully transfer heat to the inside of the base material iron during annealing to obtain uniform mechanical and physical properties in the thickness direction, it is necessary to keep it at the annealing target temperature for more than 5 seconds. In addition, when the high-temperature annealing holding time is too long, the diffusion of the alloy interfering elements through the Fe coating increases, thereby increasing the amount of surface oxides generated, resulting in a deterioration in the quality of hot-dip galvanizing, so the holding time can be limited to less than 120 seconds.
[0087] Below, refer to Figure 2 , the effect of suppressing the surface diffusion of Mn and Si during annealing of a cold-rolled steel sheet having an Fe-plated layer containing a large amount of oxygen formed based on the above content in a high dew point atmosphere is described in more detail.
[0088] Figure 2 The phenomenon occurring inside the steel plate when the temperature of the steel plate is increased according to the conditions of the present invention is schematically shown. Figure 2(a) is a schematic cross-sectional view showing a substrate iron having a Fe plating layer containing a large amount of oxygen. The substrate iron contains alloy elements such as Mn and Si, and the Fe plating layer contains 5-50 wt % of oxygen and impurities inevitably mixed in during the electroplating process, and the balance is composed of Fe.
[0089] Figure 2 (b) shows the state where the Fe-plated cold-rolled steel sheet is heated to about 300-500°C in a nitrogen atmosphere containing 1-70% H2. The surface of the Fe-plated layer containing a large amount of oxygen is slowly reduced, so that the oxygen is removed, but at the interface between the Fe-plated layer and the base iron, internal oxides such as Mn and Si diffused from the base iron and combined with the oxygen of the Fe-plated layer are generated, so that the diffusion to the surface is suppressed. In addition, the higher the temperature, the more Mn and Si diffused inside the base iron gather, and the internal oxide at the interface grows slowly. In the low temperature region of the heating step, even if the dew point in the annealing furnace is widened to -90°C to +30°C, compared with the speed at which oxygen dissociated from water vapor diffuses into the interior of the steel due to the low temperature, there is a large amount of oxygen in the Fe-plated layer and the speed at which the Fe-plated layer is reduced and released is faster, so even if the dew point in the annealing furnace is changed in the low temperature range, it is not greatly affected. Therefore, dew point control is not a very important factor in this step.
[0090] However, the amount of oxygen inside the Fe coating plays an important role. When a large amount of fine internal oxides are produced at the interface of the Fe coating and the substrate iron and inside the substrate iron in the low temperature step, the alloying elements inside the substrate iron serve as the oxide core that can continue to carry out internal oxidation. In order to generate this oxide core, it is necessary that the concentration of oxygen and alloying components is high at the same time. When more than enough oxygen is included in the Fe coating, a large amount of oxide cores are generated near the interface of the Fe coating with high oxygen concentration and the substrate iron with high alloying element concentration. However, when oxygen is hardly included in the Fe coating, the alloying elements included in the substrate iron pass through the Fe coating and form oxides on the surface. Afterwards, when the temperature is raised, the oxygen of the Fe coating is further depleted, and the diffusion of the alloying elements in the substrate iron is further aggravated, so the generation of surface oxide is increased.
[0091] Figure 2 (c) is a schematic cross-sectional view of the base iron when the temperature is raised to 500-700°C under the same reducing atmosphere. During the heating process, the dew point inside the annealing furnace is preferably controlled at -15°C to +30°C. When the temperature rises, the Fe coating is fully reduced and the oxygen concentration decreases, so the release rate of oxygen slows down. On the other hand, the rate at which the oxygen dissociated from the water vapor in the annealing furnace diffuses into the steel interior increases significantly. Therefore, when the dew point is raised from the 500-700°C region below the temperature at which the Fe coating is completely reduced, Mn and Si inside the steel can be effectively inhibited from passing through the Fe coating and diffusing to the surface.
[0092] Figure 2 (d) is a schematic cross-sectional view of a steel plate after the dew point is adjusted to -15°C to +30°C and maintained at a high temperature in the range of 600-950°C. Mn and Si continue to diffuse inside the base iron, and oxygen supplied from water vapor quickly penetrates and is supplied on the surface of the steel plate, so Mn and Si are oxidized internally. In the low temperature range, the granular Mn oxide and Si oxide generated by reacting with the oxygen of the Fe coating at the interface between the Fe coating and the base iron act as nuclei for the growth of oxides, so the internal oxides grow intensively at the interface between the Fe coating and the base iron. In addition, the diffusion rate of oxygen is faster than that of Mn and Si with large atomic sizes, so internal oxides are generated not only at the grain boundaries inside the base iron but also deep inside the grains.
[0093] In the above, the control conditions for different temperatures are described, but the most core step in the annealing process is the step of maintaining the temperature of the steel sheet at 600-950°C. Only by controlling the dew point of the atmosphere in this temperature range, the distribution of oxides inside the plated steel sheet can be effectively controlled. Of course, even if the dew point control as described above is performed in all processes before the maintaining step, no particular problems will arise. In addition, it should be noted that the above process is merely an illustration of a specific embodiment of the present invention, and the reaction mechanism of the present invention is not necessarily construed as being limited to the above description.
[0094] After the annealing step, the annealed steel sheet may be cooled. The cooling conditions in the cooling step after the annealing step do not have a significant effect on the surface quality of the final product, that is, the coating quality, and therefore, there is no need to particularly limit the cooling conditions in the present invention. However, in order to prevent oxidation of the iron component during the cooling process, an atmosphere that is at least reducing to iron may be used.
[0095] According to a specific embodiment of the present invention, the steel sheet for coating obtained according to the above process can be hot-dip galvanized to form a hot-dip galvanized layer. In the present invention, the hot-dip galvanizing method is not particularly limited.
[0096] In the present invention, any base iron having the above alloy composition can be used as the base iron of the plated steel sheet or hot-dip galvanized steel sheet according to the present invention without limitation, and therefore the method for producing the base iron is not particularly limited.
[0097] In a specific embodiment of the present invention, the Fe plating layer can be formed on the surface of the substrate iron by electroplating, and the oxygen concentration of the formed Fe plating layer can be controlled by appropriately controlling the conditions of the electroplating solution and the plating conditions.
[0098] That is, in the present invention, in order to form the Fe plating layer, an electroplating solution can be used, which contains: iron ions, wherein the iron ions include divalent iron ions and trivalent iron ions; a complexing agent; and inevitable impurities, and the concentration of trivalent iron ions in the iron ions is 5-60% by weight.
[0099] According to a specific embodiment of the present invention, the electroplating solution includes ferrous iron and ferric iron. In order to obtain high plating efficiency, it can be advantageous to only include ferrous iron, but when only including ferrous iron, the solution deteriorates and the plating efficiency is sharply reduced, so that the quality deviation in the continuous electroplating process may be caused, so the ferric iron may be further included. At this time, the concentration of the ferric iron is preferably 5-60% by weight of the sum of ferrous iron and ferric iron, more preferably 5-40% by weight. When the concentration of the ferric iron is less than 5%, the speed at which ferric iron is reduced to ferrous iron in the negative electrode is less than the speed at which ferric iron is oxidized to ferric iron in the positive electrode, so the concentration of ferric iron rises sharply, pH sharply decreases, and plating efficiency continues to decrease. In addition, when the ion concentration of ferric iron exceeds 60%, the reaction amount of ferric iron reduced to ferrous iron in the negative electrode is greatly increased compared with the reaction amount of ferrous iron being reduced and precipitated as metallic iron, so plating efficiency is greatly reduced, and plating quality is reduced. Therefore, considering the equipment and process characteristics such as the coating amount, the working current density, the solution supply amount, the amount of solution lost due to adhesion to the strip, and the concentration change rate caused by evaporation, the concentration of the trivalent iron ions in the iron ions is preferably 5-60% by weight.
[0100] The concentration of the iron ions is preferably 1-80 g per 1 L of the electroplating solution, more preferably 10-50 g / L. When the concentration of the iron ions is less than 1 g / L, there is a problem of a sharp decrease in plating efficiency and plating quality. On the other hand, when the concentration of the iron ions exceeds 80 g / L, precipitation may occur due to the excess solubility, and the loss of raw materials caused by the loss of solution in the continuous plating process increases, which is uneconomical.
[0101] The electroplating solution of the present invention contains a complexing agent. In order to prevent sludge from being generated while containing a large amount of trivalent iron and to maintain high plating efficiency, it is preferred to use an amino acid or an amino acid polymer as the complexing agent.
[0102] Amino acid refers to an organic molecule formed by the combination of a carboxyl group (-COOH) and an amino group (-NH2), and an amino acid polymer refers to an organic molecule formed by the polymerization of two or more amino acids, and an amino acid polymer shows complexing agent properties similar to those of amino acids. Therefore, in the following description, amino acids and amino acid polymers are collectively referred to as amino acids.
[0103] When amino acids are dissolved in neutral water, the amines combine with hydrogen ions to become positively charged, while the hydrogen ions of the carboxyl groups are dissociated to become negatively charged, so the amino acid molecules remain electrically neutral. In addition, when the solution is acidified, the carboxyl groups and hydrogen ions are recombined to become electrically neutral, while the amines have a positive charge, so the amino acid molecules form positive ions. In other words, amino acids form electrically neutral or positive ions in slightly acidic aqueous solutions.
[0104] When amino acids are added to an acidic electrolyte containing iron ions, the amino acids complex with divalent iron ions and trivalent iron ions, and the iron ions complexed with the amino acids remain in a positive ion state even in the complex state. Therefore, compared with conventional complexing agents with multiple carboxyl groups that carry a negative charge in a weakly acidic aqueous solution, they exhibit opposite electrical properties.
[0105] In addition, compared with complexing agents containing multiple carboxyl groups such as citric acid and EDTA, amino acids form fewer bonds with iron ions and have weaker bonding strength, but the bonding strength with trivalent iron ions that produce sludge is strong enough, so precipitation caused by trivalent iron ions can be prevented. In addition, even if trivalent iron ions are complexed, positive ions can be maintained, so trivalent iron ions are easily transferred to the negative electrode and reduced to divalent iron ions, so that they can participate in the plating reaction. On the other hand, the movement to the positive electrode is suppressed, and the generation rate of trivalent iron ions is slowed down. Therefore, even if continuous plating is performed for a long time, the concentration of trivalent iron ions is maintained at a specified level, the specified plating efficiency is maintained, and there is no need to replace the electrolyte.
[0106] In addition, in the continuous electroplating process, when the iron ions in the plating solution are exhausted, the solution is acidified, and even if the same amount of iron ions are precipitated, the pH change of the solution containing trivalent iron ions is reduced compared to the solution containing only divalent iron ions. When the pH increases, part of the trivalent iron ions are combined with hydroxide ions, and when the pH decreases, the hydroxide ions are separated and neutralized. Therefore, even if the solution containing trivalent iron ions does not have a separate pH buffer, the pH change is also slowed down, thereby playing the role of a pH buffer, and therefore, the specified electroplating efficiency can be maintained in the continuous electroplating process.
[0107] Therefore, by using an amino acid as a chelating agent, sludge can be prevented, and not only divalent iron ions but also trivalent iron ions can be used as plating raw materials. When divalent iron ions and trivalent iron ions are mixed, the pH change of the solution can be slowed down and the accumulation of trivalent iron ions can be easily prevented. Therefore, the specified plating efficiency and plating quality can be maintained in the continuous electroplating process.
[0108] In addition, the complexing agent can be added so that the molar concentration ratio of the iron ion to the complexing agent is preferably 1:0.05 to 2.0, more preferably 1:0.5 to 1.0. When the above value is less than 0.05, it is impossible to suppress the excessive ferric ion contained to be combined with hydroxide ion or oxygen to form sludge, and even if ferric iron is not included, the plating efficiency is also greatly reduced, and then combustion can be caused, so the plating quality deteriorates. On the other hand, even if the above value exceeds 2.0, the sludge suppression effect and the plating quality can also be kept, but the overvoltage increases and the plating efficiency decreases, and compared with the raw material containing iron ion such as iron sulfate, it is unnecessary to include excessive relatively high-priced amino acids, so the raw material cost increases and is uneconomical.
[0109] The complexing agent is preferably one or more selected from amino acids or amino acid polymers, for example, one or more selected from alanine, glycine, serine, threonine, arginine, glutamine, glutamic acid and glycylglycine.
[0110] When the amino acid is used as a complexing agent and the solution temperature is maintained below 80°C and the pH is 2.0 to 5.0, the concentration of 3-120 A / dm 2 When electroplating is carried out at a current density of , an Fe plating layer with high plating efficiency and high oxygen concentration can be obtained.
[0111] Although the temperature of the Fe electroplating solution has little effect on the quality of the Fe plating layer, when the temperature of the Fe electroplating solution exceeds 80°C, the evaporation of the solution becomes serious, the concentration of the solution continues to change, and it is difficult to perform uniform electroplating.
[0112] When the pH of the Fe electroplating solution is less than 2.0, the electroplating efficiency is reduced and is not suitable for a continuous plating process. When the pH exceeds 5.0, although the plating efficiency is increased, sludge of iron hydroxide precipitation is generated during the continuous electroplating process, resulting in pipeline blockage, roller and equipment pollution.
[0113] When the current density is less than 3A / dm 2 When the current density exceeds 120A / dm 2 When the coating is heated, the coating surface burns, the coating becomes uneven, and the Fe coating easily falls off.
[0114] As described above, the present invention preferably contains 5-50 wt% oxygen in the Fe coating. The reason for the mixing of oxygen in the Fe coating is as follows. In the process of iron precipitation on the surface of the steel plate to which the negative electrode is applied, hydrogen ions are simultaneously reduced to hydrogen gas, and the pH rises. Therefore, both the divalent iron ions and the trivalent iron ions are temporarily combined with OH. -Ion combination, and can be mixed together when forming the Fe coating. If anionic complexing agents such as acetic acid, lactic acid, citric acid, EDTA, etc. are used, the complexing agent and OH - The ion-bound iron ions have an average negative charge, and when the negative electrode for electroplating is applied, an electric repulsion is generated, thereby inhibiting the mixing into the Fe plating layer. On the other hand, amino acids are electrically neutral at pH 2.0 to 5.0, and have positive ions in strong acids with a pH of less than 2.0. Even if the iron ions bound to amino acids have 1-2 OH groups, - , and also carry positive ions, so it generates electrical attraction with the negative electrode for electroplating and mixes a large amount of oxygen. Therefore, when Fe electroplating is performed using amino acids as complexing agents, with a molar concentration ratio of iron ions to amino acids of 1:0.05 to 1:2.0, and pH is maintained at 2.0 to 5.0, a Fe coating containing 5-50% by weight of oxygen can be obtained while having high plating efficiency and suppressing the generation of sludge.
[0115] In order to ensure the quality of hot-dip galvanizing of steel sheets containing Mn and Si, the concentration of iron is preferably 0.5-3.0 g / m 2 The upper limit of the Fe coating amount is not particularly limited, but when it exceeds 3.0 g / m 2 When the Fe plating amount is large, multiple plating units are required or the production speed is reduced, which is not economical. In addition, when the Fe plating amount is large, the Fe plating solution in the continuous process will be rapidly degenerated, resulting in a decrease in pH and a significant decrease in plating efficiency, which makes it difficult to manage the solution. On the other hand, when the Fe plating amount is less than 0.5 g / m 2 When the Fe coating is completely reduced during annealing, the oxygen contained in the Fe coating is rapidly reduced and removed, so it is not possible to effectively suppress the diffusion of Mn and Si from the base iron and the formation of surface oxides, resulting in a problem of reduced hot dip coating quality. The Fe coating amount is the iron concentration contained in the coating, and when the Fe coating is completely reduced during annealing, it has a thickness of about 0.05-0.4 μm.
Claims
1. A steel plate having a composition comprising Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities, The GDS curve of the Mn component and the GDS curve of the Si component observed from the surface in the depth direction contain a maximum point and a minimum point respectively. The difference between the value obtained by dividing the Mn concentration at the maximum point of the GDS curve of the Mn component by the Mn concentration of the base material and the value obtained by dividing the Mn concentration at the minimum point of the GDS curve of the Mn component by the Mn concentration of the base material, i.e., the Mn conversion concentration difference is 80% or more. The difference between the value of the Si concentration at the maximum point of the GDS curve of the Si component divided by the Si concentration of the base material and the value of the Si concentration at the minimum point of the GDS curve of the Si component divided by the Si concentration of the base material, i.e., the Si conversion concentration difference is 50% or more, in, When no local point appears within a depth of 5 μm, the position at a depth of 5 μm is regarded as the position where the local point appears.
2. The steel plate according to claim 1, wherein: The steel sheet includes a base iron and an Fe plating layer formed on a surface of the base iron, and the surface is a surface of the Fe plating layer.
3. The steel plate according to claim 1, wherein: The difference in converted concentration of Mn is 90% or more, and the difference in converted concentration of Si is 60% or more.
4. The steel plate according to claim 1, wherein: The maximum point is formed at a depth of 0.05-1.0 μm.
5. A hot-dip galvanized steel sheet, comprising the steel sheet according to claim 1 to 4 and a hot-dip galvanized layer formed on the steel sheet.
6. A method for manufacturing a steel plate, comprising the following steps: preparing a base iron having a composition including, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities; Electroplating the substrate iron to form an Fe plating layer containing 5-50 wt % of oxygen; and The base iron on which the Fe plating layer is formed is annealed at 600-950° C. for 5-120 seconds in an annealing furnace in an atmosphere of 1-70% H 2 -balance N 2 gas with a dew point temperature controlled at −15° C. to +30° C.
7. The method for manufacturing a steel plate according to claim 6, wherein: The Fe coating has an adhesion of 0.5-3 g / m 2 .
8. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The complexing agent is one or more selected from alanine, glycine, serine, threonine, arginine, glutamine, glutamic acid and glycylglycine.
9. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The electroplating solution contains divalent iron ions and trivalent iron ions, the ratio of the trivalent iron ions to the total iron ions is 5-60 wt %, and the total concentration of the iron ions is 1-80 g per 1 L of the electroplating solution.
10. The method for manufacturing a steel plate according to claim 6 or 7, wherein: The electroplating process is carried out at a solution temperature of 80°C or less and a current density of 3-120A / dm 2 under the conditions of.
11. A method for manufacturing a hot-dip galvanized steel sheet, comprising the following steps: preparing a base iron having a composition including, in weight %, Mn: 1.0-8.0%, Si: 0.05-3%, C: 0.06-0.4%, Al: 0.005-3.0%, P: 0.04% or less, S: 0.015% or less, N: 0.01% or less, Cr: 1.5% or less, B: 0.005% or less, and the balance of Fe and inevitable impurities; Electroplating the substrate iron to form an Fe coating containing 5-50 wt % of oxygen; The base iron on which the Fe plating layer is formed is annealed at 600-950° C. for 5-120 seconds in an annealing furnace in an atmosphere of 1-70% H 2 -balance N 2 gas with a dew point temperature controlled at -15° C. to +30° C., thereby obtaining a steel sheet for plating; and The steel sheet for coating is immersed in a galvanizing bath.
